(untitled) (Bangladesh Journal of Nuclear Medicine, 2017)
In SPECT, data acquisition occurs over a relatively long time. During the whole acquisition time the patient must lie still, which is very difficult. Therefore, patient movement is frequently reported in clinical applications. These movements cause misalignment of the projection frames and may introduce artifacts. To overcome this, motion detection and correction techniques are applied to improve image quality. In this work, we have reviewed the detection methods for the SPECT motion. Motion detection methods are classified into two categories. These are either external or internal base motion detection. External motion detection are based on hardware using external device which also independently corrects artifacts due to motion. Motion detection data information is separate from the actual image data. Internal motion detection occurs from software or algorithm base using the measured data itself to detect motion. Both external and internal base methods are effective for motion detection in SPECT. Bangladesh J. Nuclear Med. 18(1): 54-60, January 2015